2016
DOI: 10.1017/s0305004116000657
|View full text |Cite
|
Sign up to set email alerts
|

On computing homology gradients over finite fields

Abstract: Abstract. Recently the so-called Atiyah conjecture about l 2 -Betti numbers has been disproved. The counterexamples were found using a specific method of computing the spectral measure of a matrix over a complex group ring. We show that in many situations the same method allows to compute homology gradients, i.e. generalizations of l 2 -Betti numbers to fields of arbitrary characteristic. As an application we point out that (i) the homology gradient over any field of characteristic different than 2 can be an i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…If G is an amenable group we have constructed rk G as a Sylvester matrix rank function not only on C [G] but also on K [G] for every field K. In particular, we can formulate an analogue of Atiyah's question in characteristic p: is it true that rk G takes only rational values as a Sylvester matrix rank function on F p [G]? This question was considered in [45] where it was shown that for every real number r there exists an amenable group G such that r ∈ A Fp (G). Again, as in the case of similar examples in characteristic 0, the examples of groups from [45] have finite subgroups of unbounded order.…”
Section: The Atiyah Question In Positive Characteristicmentioning
confidence: 99%
See 1 more Smart Citation
“…If G is an amenable group we have constructed rk G as a Sylvester matrix rank function not only on C [G] but also on K [G] for every field K. In particular, we can formulate an analogue of Atiyah's question in characteristic p: is it true that rk G takes only rational values as a Sylvester matrix rank function on F p [G]? This question was considered in [45] where it was shown that for every real number r there exists an amenable group G such that r ∈ A Fp (G). Again, as in the case of similar examples in characteristic 0, the examples of groups from [45] have finite subgroups of unbounded order.…”
Section: The Atiyah Question In Positive Characteristicmentioning
confidence: 99%
“…This question was considered in [45] where it was shown that for every real number r there exists an amenable group G such that r ∈ A Fp (G). Again, as in the case of similar examples in characteristic 0, the examples of groups from [45] have finite subgroups of unbounded order.…”
Section: The Atiyah Question In Positive Characteristicmentioning
confidence: 99%
“…In the second part we rebuild the computational tool from [GS14] for characteristic 2. Then corresponding to L 2 -Betti numbers of normal coverings we show, for any real number r, the construction of a finitely generated amenable group and an associated F 2 [G] matrix, whose kernel has Følner dimension r.…”
Section: Methods Of Computationmentioning
confidence: 99%
“…To showcase some calculations of the Følner dimension previously defined, we amend the results of [GS14] with the case of F 2 , the field of 2 elements.…”
Section: Graphical Representationmentioning
confidence: 99%
See 1 more Smart Citation